ANALISIS PENGARUH CITRA MEREK, KEPUASAN MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK J&T EXPRESS - Krisna Deva Pratama Sudibyo; Tri Ratna Pamikatsih (Universitas Malikussaleh, 2023)
This study aims to determine the factors that influence J&T Express brand loyalty in Boyolali. The population in this study are users or people who have used J&T Express services and the sample used is 140 respondents. The sampling technique in this study was purposive sampling. This research was conducted in Boyolali, using a questionnaire as data collection which was distributed to 140 respondents. The data analysis method used in this study is multiple linear regression, using of the statistical tool SPSS version 23. The results of the study reveal that brand trust and brand satisfaction have a positive and significant effect on brand loyalty while the brand image variable has a positive but not significant effect on brand loyalty.